Astronomical Knowledge and Cardinal Directions among the Coastal Communities of Medan amid Climate Change - Sri Rahayu; Mutiara Br Aruan; Risdo Sappe Tua Purba; Lom Lom Suwondo; Pujiati Pujiati; Muhammad Nur Nainggolan (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study examines the knowledge of constellations and cardinal directions among the Malay coastal community in Medan as part of a traditional knowledge system (Ilmu Falak) used in maritime activities and sea-based livelihoods, particularly in the context of climate change. Drawing upon the cultural framework proposed by Koentjaraningrat, Ilmu Falak is understood as an element of a knowledge system transmitted across generations and serving both practical and symbolic functions. The Malay astronomical tradition is historically connected to the development of Islamic astronomy, which flourished during the era of scholars such as Al-Khwarizmi, Al-Farghani, and Nasir al-Din al-Tusi, and was documented in classical manuscripts such as Sulalatus Salatin. This research employs a qualitative method with historical and ethnographic approaches through literature studies, interviews with coastal fishermen in Medan, and comparison with contemporary meteorological data. The findings show that Malay coastal communities utilize the positions of constellations, seasonal wind directions, lunar phases, and natural signs as guides for navigation and weather prediction. However, shifts in seasonal patterns caused by global climate change have affected the accuracy of several traditional indicators. Nevertheless, Malay astronomical knowledge still possesses adaptive value, particularly when integrated with modern scientific data. This study emphasizes that Malay Ilmu Falak is not merely a cultural heritage but also a form of ecological wisdom that remains relevant in contemporary contexts. The integration of local knowledge and modern science is essential to strengthen the resilience of coastal communities facing increasingly unpredictable climate dynamics.